Ovarian volume as an independent marker for metabolic dysfunction in women with suspected androgen excess - Roy G. Handelsman, M.D; Sahar Wertheimer, M.D; Katherine VanHise, M.D; Rae A. Buttle, B.A; Ekaterina L. Clark, B.S; Erica T. Wang, M.D., M.A.S; Ricardo Azziz, M.D., M.P.H; Margareta D. Pisarska, M.D; Jessica L. Chan, M.D., M.S.C.E (Elsevier, 2022)
Objective: To determine whether ovarian volume (OV) alone is an independent marker for metabolic dysfunction in women with suspected androgen excess. Design: Retrospective cohort study. Setting: Tertiary academic reproductive endocrinology clinic. Patient(s): Women aged ≥21 years recruited/referred for symptoms related to androgen excess. Intervention(s): Transvaginal ovarian ultrasound, physical and medical evaluation, 2-hour 75-g oral glucose tolerance test (oGTT), and blood sampling. Main Outcome Measure(s): Prevalence of hyperandrogenism and metabolic dysfunction. Result(s): This study included 666 women, of whom 412 (61.9%) and 254 had OVs of >10 and ≤10 mL, respectively. An OV of >10 mL was associated with a higher prevalence of hirsutism (65.1% vs. 51.5%) than an OV of ≤10 mL. Polycystic ovary syndrome by the National Institutes of Health 1990 criteria was found in 67.3% and 51.4% of women with OVs of >10 and ≤10 mL, respectively. Metabolic parameters, including body mass index, waist circumference, and 1-hour insulin levels during the oGTT (odds ratio, 1.98; 95% confidence interval, 1.18-3.31), were significantly higher in women with an OV of >10 mL than in those with an OV of ≤10 mL. An OV of ≤10 mL had a 76.3% negative predictive value for hyperinsulinemia at 1 hour. Conclusion(s): In women with suspected androgen excess, an OV of >10 mL in at least 1 ovary is not associated with metabolic syndrome but is associated with younger age; an increased body mass index and waist circumference; a higher prevalence of hirsutism, oligoovulation, and polycystic ovary syndrome; and a higher 60-minute insulin level during the oGTT. Overall, an increased OV appears to be a good marker for hyperinsulinemia and hyperandrogenism in women suspected of having an androgen excess disorder.